(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
A 59-year-old man had complaints of shortness of breath, thickened and dry skin especially on both hands. Results of thoracic HRCT obtained interstitial lung disease. A year after, the patient underwent geneXpert sputum test because he still complained of coughing with white phlegm and tightness while doing activity. The test obtained Mycobacterium tuberculosis 2+. He received anti-tuberculosis drugs. One month after infection, the patient was evaluated for Mycobacterium tuberculosis, while administration of antituberculosis drugs was continued for up to 8 months. In the second year, the patient had severe restriction, and was given advanced anti-tuberculosis drugs in the sixth month.